49.0k views
3 votes
Solve for x: 3(x + 1) = −2(x − 1) − 4.

1 Answer

2 votes

Answer:

Multiply the first bracket by 3

Multiply the second bracket by -2

3x+3=-2x+2-4

3x+2x+3=-2x-2 negative (-) number and positive number (+)= negative number

Just rearranging

5x+3=-2

5x+3-3=-2-3

5x=-5

Dividing by 5

5x/5=-5/5

x=-1

Check answer by using substitution method

3(-1+1)=-2(-1-1)-4

0=-2(-2)-4 negative number and negative number = positive number

0=4-4

0=0

Answer is x=-1

User Dominik Chudy
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.